2008
DOI: 10.1111/j.1469-8137.2008.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced differences in diurnal variation of carbon isotope composition of leaf respired CO2 among functional groups

Abstract: Summary The first broad species survey of diurnal variation in carbon (C) isotope signatures of leaf dark‐respired CO2 (δ13Cres) is presented here and functional differences and diurnal dynamics are linked to fractionation in different respiratory pathways, based on 13C‐labelling experiments. δ13Cres was analysed with a rapid in‐tube incubation technique in 16 species. A large diurnal increase in δ13Cres (4–8‰) occurred in evergreen, slow‐growing and aromatic species and correlated significantly with cumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
138
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(150 citation statements)
references
References 66 publications
(117 reference statements)
8
138
4
Order By: Relevance
“…At the ecosystem level, an additional factor is the fact that respiration of leaves is strongly inhibited in the light but may exhibit a marked increase with very positive δ 13 C res (LEDR) at the beginning of the dark period (Barbour et al, 2011). A maximum peak in δ 13 C res after sunset (duration of 60-100 min) was correlated with the light intensity on the prevailing day, showing higher 13 C enrichment during sunny compared to cloudy days (Barbour et al, 2011), thus confirming the patterns observed in leaves (Prater et al, 2006;Priault et al, 2009). Indeed, markedly 13 C-enriched CO 2 has been measured in tree crowns at night .…”
Section: M32supporting
confidence: 68%
“…At the ecosystem level, an additional factor is the fact that respiration of leaves is strongly inhibited in the light but may exhibit a marked increase with very positive δ 13 C res (LEDR) at the beginning of the dark period (Barbour et al, 2011). A maximum peak in δ 13 C res after sunset (duration of 60-100 min) was correlated with the light intensity on the prevailing day, showing higher 13 C enrichment during sunny compared to cloudy days (Barbour et al, 2011), thus confirming the patterns observed in leaves (Prater et al, 2006;Priault et al, 2009). Indeed, markedly 13 C-enriched CO 2 has been measured in tree crowns at night .…”
Section: M32supporting
confidence: 68%
“…This intramolecular heterogeneity of 13 C results in an 'apparent fractionation' during dark respiration depending on the balance between pyruvate dehydrogenase and Krebs cycle metabolic reactions due to the deviation of C to secondary metabolism Ghashghaie et al 2003;Werner et al 2007b;Priault et al 2009). The observed depletion in foliage d 13 C res with drought ( Fig.…”
Section: Variation In D 13 C Res Of Foliagementioning
confidence: 99%
“…Changes in either the magnitude of component fluxes or their isotope composition (d 13 C res ) may drive the observed variations in the isotopic signature of d 13 C R . Substantial temporal variations in isotopic composition of CO 2 respired by leaves (e.g., Hymus et al 2005;Mortazavi et al 2005;Kodama et al 2008;Werner et al 2007bWerner et al , 2009Priault et al 2009;Sun et al 2009), roots (e.g., Klumpp et al 2005), and soils (e.g., McDowell et al 2004a;Ekblad et al 2005;Kodama et al 2008) have been observed. Variability in photosynthetic discrimination is thought to largely determine the isotopic composition of plant as well as soil and even R eco (e.g., Ekblad and Högberg 2001;Bowling et al 2002;Mortazavi et al 2005;Werner et al 2006).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Partitioning acetyl-CoA to fatty acid synthesis and TCA leads to an overall higher contribution of PDH than TCA activity to total CO 2 efflux, which may explain the often-observed 13 C-enrichment of CO 2 efflux compared to respiratory substrate . Imbalances between TCA and PDH may also account for diel changes in δ 13 C of plant respiration (Kodama et al, 2008;Priault et al, 2009;Kodama et al, 2011). In addition, fractionation by PDH and TCA cycle enzymes may further change the isotopic signature of respired CO 2 (Tcherkez and Farquhar, 2005).…”
Section: Post-carboxylation Fractionationmentioning
confidence: 99%